Tinjauan Yuridis Tentang Hak Janda Dalam Pembagian Warisan Menurut Hukum Adat Jawa (Studi Kasus Di Pengadilan Negeri Sukoharjo) - Putri, Indah Mawarni, Septarina Budiwati, S.H., M.H, Wardah Yuspin, S.H.,M.Kn.,Ph.D (2016)
This research aims to know: (1) rights of widow in the implementation of inheritance distribution according to Javanese customary law, (2) basis of consideration of judges on the rights of widow in inheritance distribution according to customary law at the State Court of Sukoharjo. This research is a normative with a qualitative approach. The data obtained through research on the State Court of Sukoharjo. Data were collected through documents research and interviews. Technical data analysis used qualitative analysis with interactive model. The results shows that: (1) The distribution of inheritance according to Javanese customary law implemented based on the acquisition of such property during marriage. (2) basis of consideration of judges on the rights of widow in inheritance distribution according to customary law at the State Court of Sukoharjo are a) if widow do not have children, then there are two alternatives, are: (1) first settlement: congenital treasure back to the origin, because the widow is not entitled to inherit, and property acquired jointly during marriage controlled entirely by widows during life or during her unmarried with another man. (2) second settlement: congenital treasure back to the origin, and property acquired jointly during marriage directly divided into two. b) If the marriage have been blessed with children, widow inheritance on inheritance allied with children.